Analisis Struktur Ekonomi Empat Kabupaten Wilayah BARLINGMASCAKEB - Ratna Setyawati Gunawan; Diah Setyorini Gunawan (EKO-REGIONAL, 2006)
This research was aimed to observe exist or not the difference of economics structure the regencies of BARLINGMASCAKEB members. This research use secondary data with observation period 1995-2002. Data used in this research include gross regional domestic product (PDRB) with oil and gas based on the constant price in 1993. The analysis instrument used in this research is Krugman’s regional divergence index analysis. Based on the Krugman’s regional divergence index analysis can be known that there is a huge difference on the economic structure between the Cilacap Regency with the regencies of another BARLINGMASCAKEB members. The Banjarnegara, Purbalingga, Banyumas and Kebumen Regency has relative equal economic structure.Keywords: Economic structure, Krugman’s regional divergence index